A new approach to etching low‐carbon microalloyed steels to reveal prior austenite grain boundaries and the dual‐phase microstructure. (1st November 2022) - Rodriguez‐Galeano, Karol F.; Romano‐Acosta, Luis F.; Palmiere, Eric J.; Rainforth, W. Mark
Abstract: A modification to picric acid solutions has been undertaken to reveal the prior‐austenite grain boundaries in microalloyed steels as a result of elemental segregation. It has been found the maximum addition of sodium dodecyl sulphate plus hydrochloric acid to fully reveal both the prior austenite grain boundaries and the final post‐processed structures in these steels.